Gold supply risk in the ASGM engaged countries: bibliometric-based approach - Shion Yamao; Shoki Kosai; Shunsuke Kashiwakura; Eiji Yamasue; Kenichi Nakajima (Environmental Research: Infrastructure and Sustainability)
To achieve stable supply and procurement of gold, it is crucial to focus on mining activities located upstream in the supply chain and to evaluate the associated supply chain risk. This study is the first to aim to quantitatively assess the supply chain risks associated with artisanal and small-scale gold mining (ASGM) activities. Through exhaustive and non-arbitrary identification of supply chain risk factors using econometric bibliometric analysis, 16 supply chain risk factors related to ASGM activities were identified and a supply chain risk framework for ASGM was developed. Identified supply chain risk factors are categorized into social, environmental, geopolitical, economic and technological dimensions. An index-based quantitative assessment of 63 ASGM engaged countries based on the framework identified Peru, Indonesia, and Mali as high supply chain risk countries. The assessment using the methodology of this study reveals ASGM engaged countries that had been underestimated and overlooked in existing studies. The results of quantitative supply chain risk dedicated to the ASGM engaged countries could assist companies to conduct due diligence on the more strengthened gold supply chain based on responsible sourcing.